2015
DOI: 10.1007/112_2015_5001
|View full text |Cite|
|
Sign up to set email alerts
|

Intrauterine Growth Retardation (IUGR) as a Novel Condition of Insulin-Like Growth Factor-1 (IGF-1) Deficiency

Abstract: Insulin-like growth factor 1 (IGF-1) is an anabolic hormone with several biological activities, such as proliferation, mitochondrial protection, cell survival, tissue growth and development, anti-inflammatory, antioxidant, antifibrogenic and antiaging. This hormone plays an important role in embryological and postnatal states, being essential for normal foetal and placental growth and differentiation. During gestation, the placenta is one of the major sources of IGF-1, among other hormones. This intrauterine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 167 publications
2
51
0
1
Order By: Relevance
“…IGF-1 described roles include tissue growth and development, insulin-like activity, proliferation, pro-survival, anti-aging, antioxidant and neuroprotective, among others. Also, IGF-1 is a major relevant hormone in embryological and postnatal states [50]. Although it is mainly produced by the liver for endocrine activities, virtually every tissue is able to secrete IGF-1 for autocrine and/or paracrine purposes [51].…”
Section: Physiological Roles Of Insulin-like Growth Factormentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-1 described roles include tissue growth and development, insulin-like activity, proliferation, pro-survival, anti-aging, antioxidant and neuroprotective, among others. Also, IGF-1 is a major relevant hormone in embryological and postnatal states [50]. Although it is mainly produced by the liver for endocrine activities, virtually every tissue is able to secrete IGF-1 for autocrine and/or paracrine purposes [51].…”
Section: Physiological Roles Of Insulin-like Growth Factormentioning
confidence: 99%
“…Until now, the best-known conditions of IGF-1 deficiency in humans are growth hormone insensitivity (GHI), advanced liver cirrhosis and aging, including cardiovascular and neurological diseases associated to aging [52]. More recently, intrauterine growth restriction [53] and metabolic syndrome [54] seem to be other forms of IGF-1 deficiency. Besides these conditions, several diseases have been recently proposed to be either consequence or cause of both systemic or local IGF-1 deficiency [52].…”
Section: Physiological Roles Of Insulin-like Growth Factormentioning
confidence: 99%
“…Insulin‐like growth factor‐1 deficiency is associated with intrauterine growth restriction, implying the major role of IGF‐1 in normal foetal and placental growth and differentiation (Martín‐Estal, de la Garza, & Castilla‐Cortázar, ). More specifically, IGF‐1 deficiency has been shown to exert an effect on sperm count (Colombo & Naz, ) and a correlation between low sperm concentration and serum IGF‐1 levels has been reported, although no correlation was found between sperm concentration and seminal plasma IGF‐1 levels (Lee, Park, Lee, & Seo, ).…”
Section: Introductionmentioning
confidence: 99%
“…This condition may be due to both decreased insulin production by the reduced number of pancreatic islet cells and the decreased concentrations of growth hormone [18]. Mickiewicz et al [19] demonstrated that plasma GLP-2 in IUGR pigs tended to be low after birth but increased to values higher than those of the non- IGF-1 deficiency in the gestational state may be one of the major causes of fetal growth restriction [20]. IGF-1 initiates signaling pathways by binding to the IGF-1R, and is involved in numerous biological events, such as cell proliferation, migration, and inhibition of apoptosis [21].…”
Section: Pglp-2 Microspheres Improve the Pancreatic Secretion Functiomentioning
confidence: 99%